2019
DOI: 10.1136/jclinpath-2019-205891
|View full text |Cite
|
Sign up to set email alerts
|

Circular PVT1: an oncogenic non-coding RNA with emerging clinical importance

Abstract: The importance of circular RNAs (circRNAs) in pathological processes like cancer is evident. Among the circRNAs, recent studies have brought circPVT1 under focus as the most potent oncogenic non-coding RNA. Recent studies on various aspects of circPVT1, including its biogenesis, molecular alteration and its probable role in oncogenesis, have been conducted for research and clinical interest. In this review, a first attempt has been made to summarise the available data on circPVT1 from PubMed and other relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 73 publications
(74 reference statements)
1
26
0
Order By: Relevance
“…19 Up to now, the oncogenic role of circPVT1 has been confirmed in several human tumors, including OS. 23,30 There is only one report involved in the effects of circPVT1 on tumor cell metastasis, and whether this effect is mediated by EMT remains undetermined. 20 In our study, circPVT1 was found highly expressed in OS tissues and cell lines, which is consistent with the conclusion of the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…19 Up to now, the oncogenic role of circPVT1 has been confirmed in several human tumors, including OS. 23,30 There is only one report involved in the effects of circPVT1 on tumor cell metastasis, and whether this effect is mediated by EMT remains undetermined. 20 In our study, circPVT1 was found highly expressed in OS tissues and cell lines, which is consistent with the conclusion of the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…5 PVT1 gene displayed frequent amplification at genome level and concordant transcriptional up-regulation in different malignancies. 6,7 Increasing evidence has revealed the carcinogenic effects of PVT1 on various tumors, such as non-small-cell lung cancer, hepatocellular cancer, leukemia, ovarian and breast cancer. [8][9][10][11] In CRC, several studies suggested that PVT1 functioned as an oncogene to promote CRC tumorigenesis through regulating cell biological behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The biological consequences of PVT1 and circPVT1 alterations are often attributed to the downstream deregulation of MYC. Evidence obtained across hematological malignancies indicates that the regulatory role exerted on cell proliferation by PVT1 (in AML, T-ALL, BL, MM) and circPVT1 (in T-ALL, B-ALL) is mediated by MYC, as also observed in a number of solid tumors [95,96], and this regulation is active at post-transcriptional level (Fig. 3).…”
Section: Pvt1 and Circpvt1: Myc Partners In Crime And Beyondmentioning
confidence: 68%